Análisis del bienestar laboral de las mujeres en periodo de gestación y posparto en las instituciones públicas de la ciudad de Loja, año 2024 - Pijuana Erique, Tatiana Alejandra (2025)
The main objective of this research project is to conduct an evaluation of the working conditions experienced by public sector employees during their pregnancy and postpartum periods. Its purpose is to identify the main factors that impact their well-being and provide valuable perspectives on how workplace environments influence their health and overall quality of life, which is essential for shaping future policies. This study plays a crucial role in advancing the development of policies that not only protect labor rights but also prioritize the well-being of all workers. The qualitative approach used in this project involves focus groups, a method that provides a comprehensive understanding of the perceptions and knowledge of workers regarding their work environment. One of the most significant findings of the research project is that inadequate working conditions, including excessive workload and lack of institutional support, contribute to stress and negatively affect the emotional well-being of workers. In conclusion, it is crucial to implement inclusive labor policies that recognize and protect the rights of female workers within this priority group. This requires adapting workplace environments to minimize psychosocial risks and creating an environment that promotes the overall health of workers. Furthermore, it is recommended that public institutions develop clear protocols that promote workplace well-being. Key measures, such as providing breastfeeding facilities, offering flexible working hours, and implementing training programs, are essential to ensure adequate support for working mothers.